To Study Religion and Media, We Need to Teach Religion and Media Economic Realities, Challenges, and FutureDirections - Ornella, Alexander Darius (Journal for Religion, Film and Media, 2025)
Universities in the United Kingdom, and also in the United States, Austria, and Germany, are facing increased financial pressures. This has already led to the closure of religious studies departments and courses. Course closures impact not only the study choices of students but also the opportunities for the faculty to study religion and media. In this essay, written from a UK perspective, I argue that healthy recruitment into religious studies and related degrees is a necessary foundation for consideration of future directions in the study of religion and media. Given precarious funding, it is essential to consider the value that the study of religion offers the tax-paying public and how scholars in the study of religion can demonstrate how religion shapes sociocultural and political transformations. I argue that scholars of religion and media can do much to renew public interest in the study of religion.